77 Impact of Frailty on Length of Hospital Stay After Percutaneous Coronary Intervention. (31st May 2014) - Murali-Krishnan, Rachel; Iqbal, Javaid; Rowe, Rebecca; Parviz, Yasir; Sultan, Ayyaz; Gunn, Julian
Abstract : Background: Average life expectancy is rising, resulting in a higher proportion of elderly individuals being treated for coronary artery disease with percutaneous coronary intervention (PCI). PCI has benefits for this population but relatively little is known about the balance of benefit versus risk. Current PCI risk scores, such as the New York risk score, are poor predictors for elderly patients who are often frail and suffer significant comorbidities. Objective: To determine the relationship between frailty and length of hospital stay for patients undergoing PCI. Methods: Patients undergoing PCI at the South Yorkshire Cardiothoracic Centre, Sheffield, between March 2012 and January 2013, were prospectively assessed for frailty using the Canadian Study of Health and Ageing Clinical Frailty Scale (1–9, where 1 is extremely fit and 9 is pre-terminal). Patient demographics, clinical features and angiographic results were extracted from the hospital database. Mortality was obtained from the Office of National Statistics. Length of stay data were collected from hospital record as the primary outcome. Results: Frailty assessment was completed for 602 patients undergoing PCI. The median (with interquartile range) age of patients was 63 years (54–70), the frailty score was 3 (2–4) and 70.3% were males. Of these, 62 (10.3%) were deemed truly frail (frailty score of 5–7). Length of stay data were available for 576 patients. On multivariate analysis the independent risk factors for frailty were older age, female gender, hypertension, extent of coronary artery disease and the Charlson comorbidity index. Total length of stay significantly increased with increasing levels of frailty (Figure 1 ). The frailty score was a significant risk factor for increased length of stay, independently to age and the New York PCI risk score. Conclusions: A simple assessment of frailty can help predict the length of hospital stay, and may therefore help clinicians and managers plan PCI and appropriate resources for vulnerable patients.